Réponses

Meilleure réponse !
2013-10-12T22:26:04+02:00
* remplace le carré
a=2 b=6 et c=-2
1) 2x*+6x-20=0
D= b*-4ac
D= 6*-4(2)(-20)
D=36+160
D= 196 D>0 donc on a 2 solutions x1 et x2
X1=-b*- racine carré de 196 sur 2a
X1= -6-14 / 2 fois a
X1= -5
X2= -b+ racine carré de 196 sur 2a
X2= -6+14 / 2a
X2= 2
Donc S={-5 ; 2}

2) 2x*+6x-20
2(x*+6x/2-20/2)
2[(x+6/4)* - (6/4)* - 20/2]
2[(x+6/4)* - 36/16 - 160/160)
2[(x+6/4)* - 196/16]
2(x+6/4-14/4) (x+6/4+14/4)
2(x-8/4) (x+20/4)
2(x-2) (x+5)
3) jtableau 8= l'infini
------------|--------------------------------------------|
X | -8 -5 2 +8 |
-------------|----------|--------------|------------------|
| + 0 - 0 + | 2x*+6x-20 | | | |
----------------------------------------------------------